John Marchmont's Legacy, Volumes 1-3 - Braddon, M. E. (Mary Elizabeth), 1835-1915 (Salt Lake City, UT : Project Gutenberg, 2010)
"John Marchmont's Legacy, Volumes 1-3" by M. E. Braddon is a novel written in the mid-19th century. The story revolves around Edward Arundel, a young protagonist who navigates societal expectations and personal challenges, particularly as he becomes intertwined with the fate of his former mathematics tutor, John Marchmont, whose fortunes have taken a tragic turn. As Edward develops a friendship with John and his precocious daughter, Mary, the narrative hints at themes of familial legacy, social class, and the pursuit of happiness amidst adversity. The opening of the novel introduces Edward Arundel, who, as a carefree schoolboy, attends a play with his cousin. During the performance, he recognizes his old tutor, John Marchmont, now a struggling stage supernumerary. This recognition sets the stage for a deeper relationship, as Edward$1 (Bs compassion drives him to seek out John and offer assistance. John's plight is compounded by his concern for his daughter, Mary, who embodies the innocence and resilience of a child burdened with adult worries. Through Edward's earnest intentions and John's lamentations about their shared heritage, readers are drawn into a world where personal aspirations clash with the harsh realities of life, hinting at complex future interactions shaped by societal pressures and hidden intimate ties. (This is an automatically generated summary.)s
Release date is 2010-12-01
Produced by Clare Graham, using scans from the Internet Archive
Keywords: Triangles (Interpersonal relations) -- Fiction; Children of clergy -- Fiction; Lincolnshire (England) -- Fiction; Women intellectuals -- Fiction